MANFAAT MASKER BUAH PARE UNTUK MENGURANGI KERONTOKAN RAMBUT PADA IBU NIFAS - Enma Megawati; Dwi Anjani, Arum (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2025)
ABSTRACT The postpartum period is a complex physiological and psychological adaptation period in postpartum women, characterized by hormonal changes that can trigger various complaints such as hair loss, which if left untreated can cause anxiety, so that proper understanding and handling are needed such as the use of natural ingredients, one of which is a bitter melon fruit mask, which is known to contain antioxidants, vitamins, and other active compounds that have the potential to reduce hair loss safely and naturally, especially in postpartum mothers. The purpose of this study was to determine the benefits of bitter melon fruit masks to reduce hair loss in postpartum mothers. Research method This study is a quantitative study with a pre-experimental design that aims to determine the effect of bitter melon fruit masks on hair loss in postpartum mothers at the UPTD Puskesmas Sri Bintan 2025, with a sample size of 30 respondents. Data analysis used the Independent T-Test if the data was normally distributed, and the Wilcoxon test if it was not normal. Results and Conclusions The Wilcoxon test showed that 26 respondents experienced a decrease in hair loss, 4 did not change, and none increased, with a Z value = -4.495 and p < 0.001, so there was a significant difference before and after treatment with a decrease in direction Keywords : Mask, Bitter melon, Hair loss, Postpartum mothers